An Introduction to English Semantics and Pragmatics - Griffiths, Patrick 1942-2012 (Edinburgh textbooks on the English language, 2023)
A classic introduction to the study of meaning, revitalised for a new generation of linguistsIdeal for undergraduate students exploring English linguistics for the first time, the new edition of this successful textbook is compact and self-contained, offering:Expanded coverage of topic areas such as figurative language, compositional meaning and quantificationUp-to-date, real-life examples drawn from a wide range of sources to clearly illustrate key concepts, such as how speakers use novel metaphors and metonymsAdditional exercises to further reinforce and develop key conceptsThorough signposting to contemporary research publications in semantics and pragmaticsThis clear and accessible textbook introduces the crucial concepts essential to your study of the semantics and pragmatics of English. Coverage is wide-ranging, taking you from word meaning to the level of discourse, and explaining how these topics are treated in contemporary linguistic research. Chapters cover adjective, noun and verb meanings, situation types, figurative language, tense, aspect, modality, quantification, topic and focus. Explanations of entailment, compositionality and scope provide a foundation for subsequent study of formal semantics.Supported by chapter summaries and with plenty of usage examples, exercises and discussion questions, you will not only gain a systematic overview of meaning in English but be equipped with the tools to argue for specific analyses as well